1992
DOI: 10.1038/ng0492-11
|View full text |Cite
|
Sign up to set email alerts
|

Maternally transmitted diabetes and deafness associated with a 10.4 kb mitochondrial DNA deletion

Abstract: Diabetes mellitus (DM) is one of the most common chronic disorders of children and adults. Several reports have suggested an increased incidence of maternal transmission in some forms of DM. Therefore, we tested a pedigree with maternally transmitted DM and deafness for mitochondrial DNA mutations and discovered a 10.4 kilobase (kb) mtDNA deletion. This deletion is unique because it is maternally inherited, removes the light strand origin (OL) of mtDNA replication, inhibits mitochondrial protein synthesis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
256
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(257 citation statements)
references
References 29 publications
0
256
0
1
Order By: Relevance
“…At 0400 hours of each inpatient period, a priming dose of L-[1,2-13 C]leucine (1.8 mg͞kg of FFM) was administered through a peripheral forearm vein. This was followed by a continuous infusion of L- [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]leucine (1.8 mg͞kg of FFM per h). Insulin [1.5 milliunits (mU)͞kg of FFM per min] or normal saline infusion was randomized and began at 0700 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 0400 hours of each inpatient period, a priming dose of L-[1,2-13 C]leucine (1.8 mg͞kg of FFM) was administered through a peripheral forearm vein. This was followed by a continuous infusion of L- [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]leucine (1.8 mg͞kg of FFM per h). Insulin [1.5 milliunits (mU)͞kg of FFM per min] or normal saline infusion was randomized and began at 0700 hours.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effect of insulin on skeletal muscle mitochondrial function and oxidative capacity have not been defined. Previous studies have suggested a relationship between insulin action and the oxidative capacity of skeletal muscle (3)(4)(5)(6)(7)(8)(9)(10). For example, the ratio between oxidative and glycolytic enzyme activities is decreased in skeletal muscle from type 2 diabetic subjects compared with nondiabetic subjects (6).…”
mentioning
confidence: 99%
“…[24][25][26] An increased frequency of these extensively deleted genomes may be associated with pathological states, although they exist in normal tissue. 27 These deletions may persist as partial duplications, or may be generated at a high frequency.…”
Section: Light-strand Origins Of Replicationmentioning
confidence: 99%
“…In 1992, linkage was described between mitochondrial DNA mutations and diabetes for both a deletion [64] and a point mutation [65]. The mitochondrial genome is a compact doublestranded DNA containing almost exclusively coding regions.…”
Section: Role Of Mitochondrial Dna In Insulin Secretionmentioning
confidence: 99%